Cardiac arrhythmia assessment with patch electrocardiogram versus insertable cardiac monitor: a cohort study in endurance athletes with atrial fibrillation - Trygve Berge; Andre La Gerche; Bente Morseth; Maja-Lisa Løchen; Arnljot Tveit; Marius Myrstad; Jon Magne Letnes; Guido Claessen; Bjarne Martens Nes; Turid Apelland; Kristoffer Robin Johansen; Eivind Sørensen; et al. (BMJ Open)
Objectives The objective of this study was to assess the quality of ECG recordings and the concordance between the automatic detection of cardiac arrhythmia episodes by a patch ECG and an insertable cardiac monitor.Design Prospective cohort study.Setting and participants Endurance athletes diagnosed with paroxysmal atrial fibrillation (AF) and no other relevant comorbidities participating in a randomised controlled trial on the effects of training adaption.Methods A patch ECG (ECG247 Smart Heart Sensor) was sent to 29 non-elite endurance athletes with clinical paroxysmal AF. ECG247 continuously monitors, detects and categorises cardiac arrhythmias. The participants were simultaneously monitored with an insertable cardiac monitor (Confirm Rx, Abbott). ECG recording quality was assessed by an experienced physician. Training sessions were monitored using sports watches.Results Out of 29 invited athletes, 14 athletes (mean age 60.4 years, 2 women) made use of the patch ECG and were monitored for a total of 2987 hours and a median of 14 (range 1–17) days. During this period, the athletes performed a total of 112 training sessions. ECG quality varied between athletes and by type of exercise, with poor quality in 16% and 40% of recordings during cross-country skiing and running, respectively. In two athletes, the patch ECG detected AF episodes that were confirmed with insertable cardiac monitor recordings. One technical artefact was falsely classified as ventricular tachycardia by the ECG247 Smart Heart Sensor system.Conclusion Monitoring with patch ECG was feasible in endurance athletes, but ECG recording quality varied between athletes and by type of exercise.Trial registration NCT04991337 (for the related randomised controlled trial).